From local wisdom to community-based governance: Managing mangrove ecotourism in Aceh, Indonesia - Akmal Saputra; Masrizal Masrizal; Nodi Marefanda; Herizal Herizal; Ahmad Harakan (Center for Sociological Studies and Community Developmen, 2026)
This study examines how local wisdom functions as a constitutive element of community-based governance in mangrove ecotourism in Aceh, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, document analysis, and focus group discussions involving stakeholders from government, customary institutions, communities, and the private sector. The findings demonstrate that cultural practices such as meuseuraya, duek pakat, and peumulia jamee operate as constitutive governance mechanisms that structure collective action, decision-making, and socio-ecological relations. Governance emerges not as a fixed institutional arrangement, but as a relational and negotiated process shaped by the interaction of cultural norms, institutional configurations, and power dynamics. The coexistence of customary and formal systems produces hybrid governance structures that enable coordination while generating tensions, asymmetries, and contested outcomes. This study reconceptualizes local wisdom as governance infrastructure, demonstrating that governance outcomes are not solely determined by institutional design, but are mediated by culturally grounded meanings and socially structured power relations. The results underscore that effective community-based governance depends on the institutionalization of culturally grounded practices, inclusive deliberative processes, and relational coordination across actors. These insights contribute to advancing socio-ecological systems and social capital perspectives by foregrounding culture as an operational mechanism of governance, while offering practical direction for designing context-sensitive and adaptive governance strategies in ecotourism settings.